Homozygous Deletions and Recurrent Amplifications Implicate New Genes Involved in Prostate Cancer - Liu, Wennuan (Neoplasia Press Inc., 2008)
Prostate cancer cell lines provide ideal in vitro systems for the identification and analysis of prostate tumor suppressors and oncogenes. A detailed characterization of the architecture of prostate cancer cell line genomes would facilitate the study of precise roles of various genes in prostate tumorigenesis in general. To contribute to such a characterization, we used the GeneChip 500K single nucleotide polymorphic (SNP) array for analysis of genotypes and relative DNA copy number changes across the genome of 11 cell lines derived from both normal and cancerous prostate tissues. For comparison purposes, we also examined the alterations observed in the cell lines in tumor/normal pairs of clinical samples from 72 patients. Along with genome-wide maps of DNA copy number changes and loss of heterozygosity for these cell lines, we report previously unreported homozygous deletions and recurrent amplifications in prostate cancers in this study. The homozygous deletions affected a number of biologically important genes, including PPP2R2A and BNIP3L identified in this study and CDKN2A/CDKN2B reported previously. Although most amplified genomic regions tended to be large, amplifications at 8q24.21 were of particular interest because the affected regions are relatively small, are found in multiple cell lines, are located near MYC, an oncogene strongly implicated in prostate tumorigenesis, and are known to harbor SNPs that are associated with inherited susceptibility for prostate cancer. The genomic alterations revealed in this study provide an important catalog of positional information relevant to efforts aimed at deciphering the molecular genetic basis of prostate cancer.